Anti-inflammatory efficacy of a single posterior subtenon injection of triamcinolone acetonide versus prednisolone acetate 1% eyedrops after pars plana vitrectomy - Paccola, Leticia (2007)
Purpose: To compare the safety and anti-inflammatory efficacy of a single posterior subtenon injection of triamcinolone acetonide (TA) with prednisolone acetate 1% eyedrops after pars plana vitrectomy (PPV).Methods: the study included 40 consecutive phakic eyes of 40 patients undergoing PPV for non-clearing vitreous haemorrhage with attached retina (verified by echography), epiretinal membrane or macular hole. At the end of the surgical procedure, eyes were randomized to receive either a single posterior subtenon injection of TA (40 mg in 1 ml) plus sham eyedrops (prednisolone acetate 1% vehicle) postoperatively (group TA), or a posterior subtenon sham injection (1 ml balanced salt solution) plus prednisolone acetate 1% eyedrops postoperatively (group ED).Results: There was no difference in the severity of anterior chamber cell and flare between the two groups at any time-point during the study period (p > 0.05). Separate within-group analysis revealed a significant decrease in anterior chamber cell and flare from postoperative day 1 to postoperative days 7, 14 and 28 in both groups (p < 0.05). There was no difference in pain, photophobia, conjunctival erythema, ciliary flush or chemosis scores between the two groups at any time-point during the study period (p > 0.05). Steroid-induced intraocular hypertension was not observed in either group.Conclusions: A single posterior subtenon injection of TA can be as effective and safe as a 4-week regimen of prednisolone acetate 1% eyedrops in controlling intraocular inflammation after PPV.